2009
DOI: 10.1128/cvi.00111-09
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Novel DosR Regulon-Encoded Candidate Antigens of Mycobacterium tuberculosis in Three High-Burden Populations in Africa

Abstract: Increasing knowledge about DosR regulon-encoded proteins has led us to produce novel Mycobacterium tuberculosis antigens for immunogenicity testing in human populations in three countries in Africa to which tuberculosis (TB) is endemic. A total of 131 tuberculin skin test-positive and/or ESAT-6/CFP10-positive, human immunodeficiency virus-negative adult household contacts of active pulmonary TB cases from South Africa (n ‫؍‬ 56), The Gambia (n ‫؍‬ 26), and Uganda (n ‫؍‬ 49) were tested for gamma interferon res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
140
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 146 publications
(157 citation statements)
references
References 36 publications
(39 reference statements)
14
140
1
2
Order By: Relevance
“…The present results confirm that a cellular immune response to these latency antigens can be found in vitro, and show that this response can also be efficiently detected by means of a wholeblood 1-day assay. It was also found that the response to Rv2628 antigen was more clearly associated with a latent infection, as previously shown using other experimental approaches by LEYTEN et al [14] and BLACK et al [16] and confirmed by ROUPIE et al [26] in mice. However, from all of the studies reported, it is presently unclear why the response to Rv2628 may provide better discrimination between the different stages of TB infection.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The present results confirm that a cellular immune response to these latency antigens can be found in vitro, and show that this response can also be efficiently detected by means of a wholeblood 1-day assay. It was also found that the response to Rv2628 antigen was more clearly associated with a latent infection, as previously shown using other experimental approaches by LEYTEN et al [14] and BLACK et al [16] and confirmed by ROUPIE et al [26] in mice. However, from all of the studies reported, it is presently unclear why the response to Rv2628 may provide better discrimination between the different stages of TB infection.…”
Section: Discussionsupporting
confidence: 80%
“…However, from all of the studies reported, it is presently unclear why the response to Rv2628 may provide better discrimination between the different stages of TB infection. Among the studies performed on human samples [14][15][16][17], SCHUCK et al [15] did not show any immunogenic activity of Rv2628. This may probably be due to the selection of LTBI subjects that have not been clearly defined as recently or remotely infected.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…T-cell can response to three DosR antigens, namely Rv1733c, Rv2029c, Rv2031c, the top 10 most frequently recognized Mtb DosR proteins in Mtb-exposed individuals [Black et al, 2009;Commandeur et al, 2011;Leyten et al, 2006;Schuck et al, 2009]. Strong DosR antigen-specific single and double functional CD4 þ and CD8 þ T-cell responses are detected in LTBI.…”
Section: Immunological Feature Of Dosr Regulonmentioning
confidence: 99%